EVALUATION OF DRUG PLANNING AND PROCUREMENT AT THE HEALTH OFFICE OF KEPULAUAN MERANTI REGENCY - Heriati, Melna; Seftika Sari; Husnawati (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2025)
Inability to properly plan drug needs at the health department level affects drug availability in public health services. This study aims to evaluate the drug planning and procurement process at the Health Office of Kepulauan Meranti Regency. This is a descriptive qualitative research using a case study approach. Data were collected through in-depth interviews, observations, and document reviews from the Pharmaceutical Installation Unit. The findings show that planning was not data-driven, and the Integrated Drug Planning Team (TPOT) has not been formally established. Distribution was conducted without synchronization with actual needs in primary health centers. The study concludes that strengthening information systems, improving human resources capacity, and forming an active TPOT are essential to ensure efficient drug procurement.